Flash-based interactive learning of fundamental fourier analysis - Thaiupathump T. (2014)
The interactive approach to teaching basic Fourier concepts and operations, which include basic properties of sinusoidal signals, Fourier series, sampling, aliasing, convolution, and modulation, is described. Macromedia Flash MX , which currently is a standard for the interactive animation for the Web, is used to implement the interactive teaching approach. The developed tutoring system will utilize animation contents and maximize the interaction with students for distance education as well. The ability to readily observe the results of operations after changing parameters provides learners with a better understanding of fundamental Fourier concepts.